The role of mean platelet volume predicting acute exacerbations of cystic fibrosis in children - Uysal, Pιnar (Medknow Publications, 2011)
OBJECTIVE: The aim of this study is to evaluate the relationship between acute exacerbations and the mean platelet volume (MPV) trend in children with cystic fibrosis (CF), to predict the exacerbations. METHODS: A total of 46 children with CF and 37 healthy children were enrolled in the study. White blood cell count (WBC), hemoglobin level, platelet count, mean platelet volume (MPV), and mean corpuscular volume (MCV) were retrospectively recorded. RESULTS: Our study population consisted of 25 (54.3%) males and 21 (45.7%) females with CF and 20 (54.0%) males and 17 (46.0%) females in the healthy control group. The mean age of the CF patients was 6.32 ± 4.9 years and that of the healthy subjects was 7.02 ± 3.15 years. In the acute exacerbation period of CF, the MPV values were lower and WBC and platelet counts were higher than those in the healthy controls (P = 0.00, P = 0.00, P = 0.00, respectively). Besides, in acute exacerbation, the MPV values were lower and the WBC count was higher than the values in the non-exacerbation period (P 0= 0.01, P = 0.00, respectively). In the non-exacerbation period MPV was lower and platelet count was higher when compared to healthy subjects (P = 0.02, P = 0.04, respectively). CONCLUSION: This study suggests that MPV might be used as a simple, cost effective, diagnostic, predictive indicator for platelet activation in pediatric CF patients related to chronic inflammation, which might be helpful to discriminate or estimate exacerbations.